1997
DOI: 10.1083/jcb.137.6.1393
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of Phosphorylation of Occludin in Tight Junction Formation

Abstract: Occludin is an integral membrane protein localizing at tight junctions in epithelial and endothelial cells. Occludin from confluent culture MDCK I cells resolved as several (>10) bands between 62 and 82 kD in SDS-PAGE, of which two or three bands of the lowest M r were predominant. Among these bands, the lower predominant bands were essentially extracted with 1% NP-40, whereas the other higher M r bands were selectively recovered in the NP-40–insoluble fraction. Alkaline phosphatase treatment converged these b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

33
394
3
4

Year Published

1999
1999
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 534 publications
(440 citation statements)
references
References 46 publications
33
394
3
4
Order By: Relevance
“…The most abundant of the forms had an apparent molecular mass of 62±66 kDa, close to the predicted molecular mass of the unmodified protein. Recent studies have suggested that occludin may undergo function-dependent modifications and that it may be the "heavy", possibly phosphorylated, forms of occludin that seal TJs [33,34]. The human airway cell lines expressed heavy forms of occludin (bands of~72±74 kDa were detectable in both cell lines with a protein of 94 kDa additionally present in Calu-3 cells), although the authors are unable to comment on their phosphorylation status.…”
Section: Discussionmentioning
confidence: 97%
“…The most abundant of the forms had an apparent molecular mass of 62±66 kDa, close to the predicted molecular mass of the unmodified protein. Recent studies have suggested that occludin may undergo function-dependent modifications and that it may be the "heavy", possibly phosphorylated, forms of occludin that seal TJs [33,34]. The human airway cell lines expressed heavy forms of occludin (bands of~72±74 kDa were detectable in both cell lines with a protein of 94 kDa additionally present in Calu-3 cells), although the authors are unable to comment on their phosphorylation status.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, several studies have demonstrated the involvement of various kinases in the phosphorylation and regulation of claudin proteins [29][30][31][32][33][34][35][36][37], and we have recently shown that phosphorylation of claudin-3 by PKA can affect TJ properties in ovarian cancer cells [38]. Protein kinase C (PKC) isoforms are present in ovarian cancer and are known to modulate TJ function by phosphorylation of the proteins in the complex [24,34,[39][40][41][42][43], but it is unclear whether PKC can directly phosphorylate and regulate claudin proteins. We have previously shown that claudin-4 can be phosphorylated in ovarian cancer cells upon 12-OTetradecanoylophorbol-13-acetate (TPA) stimulation [38], but the exact PKC isoforms involved, the phosphorylation sites on claudin-4, and the consequences of this phosphorylation have remained unknown.…”
Section: Introductionmentioning
confidence: 99%
“…4. Test for the possibility that the early increase in TER, observed after addition of MBCD, might be associated with an increase of phosphorylated occludin, which has previously been shown to be present in epithelia with high, but not low TER [16].…”
Section: Introductionmentioning
confidence: 99%